Adverse Human Health and Environment of Pig Farming with Cost Benefit in the Mid-Terai of Nepal - Ghimire, Mayanath; Bolar, Jaishree; Aithal, P. S.; Shrestha, Kiran; Shrestha, Arjun (GS WOW: Wisdom of Worthy Research Journal, 2024)
The pig farming have adverse impact in human health and environment in the society and cost benefited from pig farming in Nepal. The research utilized a scientific review process known as meta-analysis to examine articles related to pig farming, disease, meat and piglet marketing, and sanitation synthesizing the information. Thorough archival analysis paired with a comprehensive review would be the strategies employed for the scientific review of systematic manner by gathering research papers, reports, and data. The socioeconomic situation of the pig farmers is really dire. They don't understand the importance of hygiene and health. Eighty percent of farmers in Terai districts keep their pigs in the open. The pig rearing majority of households in the communities that raise pigs lack latrines. They defecate in an open field. Pigs are typically fed hotels waste across Nepal. The pig rearing sheds are dirty and it make environment polluted and help transform disease to human. Farmers are unaware of the parasites and diseases afflicting pigs since they do not make a lot of effort to maintain the health of the native pigs. In Nepal, pigs can be affected by diseases such as swine fever, roundworm and tapeworm, as well as external parasites like lice, and myiasis. The zoonotic transformed disease and parasites harm to human also. Pig farming ranked around 3rd or 4th place among the sources of household income in Nepal and India sale from meat and piglet’s especially in eastern area of Nepal from local Dharane black pork.